Changes in bursal B cells in chicken during embryonic development and early life after hatching. Issue 1 (December 2018) - Ko, Kwang; Lee, In; Kim, Girak; Gu, Min; Kim, Hyun; Park, Byung-Chul; Park, Tae; Han, Seung; Yun, Cheol-Heui
Abstract The bursa of Fabricius, the primary lymphoid organ for B cell development found only in birds, offers novel approaches to study B cell differentiation at various developmental stages. Here, we explored the changes and mechanism involved in the developmental stages of bursal B cells. The bursal B cells rapidly increased in the late embryonic stage and around hatching, which coincided with changes in specific cell surface markers. Moreover, the cells in the bursa were divided by size into small (low forward- and side-scatter) or large (high forward- and side-scatter) via flow cytometry. It is intriguing that the proportion of small and large B cells was reversed during this period. Because little is known about this phenomenon, we hypothesized that size-based B cell population could be used as an indicator to distinguish their status and stage during B cell development in chicken. The results demonstrated that large B cells are actively proliferating cells than small B cells. Additionally, large B cells showed higher mRNA expression of both proliferation- and differentiation-associated genes compared to small B cells. Taken together, these data show that large bursal B cells are the main source of proliferation and differentiation during B cell development in chickens.